Interactions of Little-brain and Big-brain in Explaining Abdominal Symptoms - Yeh Lee, Yeong; Ramasami , Naveen (International Journal of Endorsing Health Science Research, 2022)
For a long time, the role of an extensive neurological network in the gut (the little-brain) has been under-recognized because the enteric nervous system (ENS) is thought to have little impact beyond digestion. More recently, there has been a paradigm shift in understanding interactions between the gut and brain, i.e., the gut-brain axis, especially in clinical disorders termed functional gastrointestinal disorders (FGIDs).